2006
DOI: 10.1002/ppul.20345
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Recombinant Alpha1-Antitrypsin Therapy in Cystic Fibrosis

Abstract: Neutrophil elastase (NE) is thought to be the most important protease which damages the cystic fibrosis (CF) lung. Attempts have been made to suppress this activity using the plasma-derived inhibitor, alpha(1)-antitrypsin (AAT). In this pilot study, the safety and efficacy of inhaled recombinant human AAT (rAAT) as a treatment for CF were investigated. Thirty-nine patients participated in a prospective, double-blinded, randomized, placebo-controlled phase II trial to examine the effect of rAAT (500, 250, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
82
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 23 publications
3
82
0
2
Order By: Relevance
“…Two phase II trials of a1AT in CF have been completed (Martin et al, 2006. Both studies were prospective but had different experimental designs, different doses of inhaled a1AT, different subject populations, and evaluated different outcomes (Table 3).…”
Section: Anti-inflammatory and Antiprotease Therapies In Cfmentioning
confidence: 99%
See 1 more Smart Citation
“…Two phase II trials of a1AT in CF have been completed (Martin et al, 2006. Both studies were prospective but had different experimental designs, different doses of inhaled a1AT, different subject populations, and evaluated different outcomes (Table 3).…”
Section: Anti-inflammatory and Antiprotease Therapies In Cfmentioning
confidence: 99%
“…Clinical Trials of a1AT in CF Study Design Subjects Results (McElvaney et al, 1991) 12 CF subjects ↑ ASL a1AT Open label aerosol a1AT (1.5-3 mg/kg) 12 healthy subjects (C) ↑ ASL anti-NE mean age: 28 yrs (CF); 29 yrs (C) capacity when every 12 h for 1 week PFTs: Moderate obstruction a1AT ≥ 8 μM (Martin et al, 2006) 39 CF (32 male) ↓ NE/a1ATcomplex Prospective, randomized, Double-blind, placebo-controlled mean age: 27.5 yrs. ↓ myeloperoxidase Aerosol a1AT:125, 250 or 500 mg/day × 4 weeks PFT: Moderate obstruction ↓ NE Sputum measures compared to placebo Good safety profile 52 …”
mentioning
confidence: 99%
“…In a second study, 4 weeks of treatment with recombinant a1AT (ra1AT) made in sheep produced significant decreases in neutrophil infiltration, and reduced complexes between NE and endogenous a1AT, suggesting that ra1AT was effective in neutralizing endogenous NE. 27 Favorable results have also been collected from nebulized a1AT therapy studies in animal models. 28 Together these results suggested that a1AT aerosol treatment would benefit CF patients.…”
Section: -22mentioning
confidence: 99%
“…Both studies found decreased inflammation associated with lowered cytokines and neutrophil cell numbers. 26,27 Griese et al compared peripheral lung versus the bronchial deposition of aerosolized prolastin (a1AT purified from plasma; Bayer Corporation, Clayton, NC, USA). Although no difference was observed between the two sites of treatment deposition, both groups receiving 4 weeks of daily prolastin exhibited significant decreases in IL-8, TNFa, IL-1b protein and LKTB 4 concentrations in sputum.…”
Section: -22mentioning
confidence: 99%
“…Proteinase 3 (PR3) is secreted from activated neutrophils and is critically involved in bacterial defense but also regulates non-infectious inflammatory processes by inducing endothelial cell apoptosis and modulating the activities of cytokines including TNF-α, IL-1β, IL-8, IL-18 and IL-32 [42][43][44][45][46][47][48] Recent studies further suggest that PR3, as well as other NSPs, namely neutrophil elastase (NE) and cathepsin G (CG) contribute to neutrophil-dependent inflammation and progression of chronic inflammatory diseases including T2DM, cystic fibrosis and glomerulonephritis [49][50][51][52]. Conversely, NSP inhibitors such as α-1-antitrypsin (AAT) have been proposed as treatments in patients with chronic inflammatory diseases including diabetes, cystic fibrosis and ischemic heart disease [28,[53][54][55][56].…”
Section: Neutrophil Serine Proteases and Inflammationmentioning
confidence: 99%